Cocoa and cocoa-derived products : dietary polyphenols and beyond. - Mhd Jalil, Abbe Maleyki; Ismail, Amin (Nova Science Publishers, 2012)
In 1737, the cocoa tree was named Theobroma cacao L. which refers to the mythical background of the tree literally means “cocoa, food of the gods”. Cocoa and their related products derived from this tree had been used by our ancestors to treat various types of ailments. In the 17th and 18th century, cocoa was regularly prescribed or mixed into medications for all sorts of ailments and diseases from colds and coughing, to promote digestion, fertility, reinforce mental performance and as an anti-depressant. The empirical findings of cocoa and cocoa-derived products on health benefits were uncovered only in the 21st century owing to their exemplary amount of dietary antioxidants (flavonoids). Scrumptious taste and their roles in combating risk factors for chronic diseases are the two main reasons that staggered most of the modern scientists. Up-to-date there were vast array of scientific evidence published on the contribution of cocoa and cocoa-derived products towards health. Studies originated from in vitro, in vivo and human clinical trials strongly supported that polyphenols especially flavonoids present in cocoa and their products were absorbable and made bioavailable in the digestive system; and exerted multiple health benefits in reducing disease risk factors, preventing disease progression and ameliorating disease severity. This chapter is then delineated an insight of cocoa polyphenols’ chemistry and their putative effects on our health.